Decreased feeding rates of the copepod Acartia tonsa when exposed to playback harbor traffic noise - Kühn, Saskia; King, Franziska; Heubel, Katja (Frontiers in Marine Science, 2023)
Introduction Copepods present the largest and most diverse group of zooplankton and their feeding behavior can affect top-down and bottom-up processes. Thus, how efficient feeding is executed determines the abundance of copepods’ prey and their predators and, with that, carbon transfer and storage in ecosystems. The rise of anthropogenic underwater noise from shipping, oil exploration and exploitation, wind farm construction and operation, and more, is increasingly changing the marine acoustic environment. This acoustic pollution can have detrimental effects on biological life. Studies on this topic increasingly indicate that anthropogenic underwater noise adversely affects primary producers, marine mammals, fish, and invertebrates. However, little data exist on the effects of anthropogenic underwater noise on the feeding behavior of zooplankton. Methods Here, we investigated the ingestion and clearance rates of the copepod Acartia tonsa on a motile phytoplankton as a function of prey density under ambient aquarium sound conditions and, when exposed to playback, harbor traffic noise. Results We measured significantly decreased ingestion rates and clearance rates of A. tonsa when exposed to harbor noise compared to ambient conditions. The negative impact of noise on the ingestion rates was found at all given phytoplankton cell densities between 1k to 10k cells ml−1. Clearance rates were fitted to the Rogers random predator equation which revealed significantly decreased capture rates on phytoplankton under the exposure of harbor noise while handling times remained the same in both sound treatments. Discussion Our results call for follow-up studies to focus on noise driven community-effects in field experiments to confirm laboratory results and to predict the outcome of a changing world with multiple stressors. Further, the underlying mechanism on how noise affects the feeding behavior of copepods is still unknown. Noise may distract copepods or mask hydromechanical cues of the prey. Noise may also adversely affect copepod physiology or morphology that would lead to changes in the feeding behavior. All potential mechanisms need to be investigated rigorously in future experiments.